The Life of Imam Al-Buqai and his Methodology in (Systems of Pearls) - an Objective Study - (Islamic Sciences Journal, 2023)
Imam Al-Buqai, may Allah have mercy on him, was one of the prominent scholars of the eighth century AH.- He suffered from his opponents harm and slander until some of them reached the point of wasting their blood and wasting their lives.Imam Al-Buqai, may Allah have mercy on him, was very intelligent, having issued a fatwa at the age of twenty.- Imam Al-Buqai, may Allah have mercy on him, composed dozens of books, compilations and books, which are considered precious gems for students of knowledge in general and for scholars in particular.- Imam Al-Buqai, may Allah have mercy on him, is not infallible from error and omission in his jurisprudence, and his words are subject to research and scrutiny, because infallibility is only for God Almighty and his messengers (peace be upon them)
Keywords: Imam Al-Buqai, his sheikhs, praise of scholars, the position of scholars, objections